Study of the growth and yield of mung bean plants (Vigna radiata L.) on the inhibitory power of ZPT Paclobutrazol - Christa Dyah Utami; Febriyanti, Icha (KHD Production, 2025)
The decline in productivity of mung beans (Vigna radiata L.) in Indonesia requires strategic efforts to increase yields. One approach studied in this study is the use of plant ZPT Paclobutrazol as a compound that inhibits vegetative growth, especially in the formation of branches that play an important role in plant yields. The purpose of this study was to determine the effect and magnitude of the inhibitory power of Paclobutrazol on the growth and yield of mung beans. The study was conducted in July–October 2024 in Sumbersari District, Jember Regency with an altitude of 160 meters above sea level. The design used was a Randomized Block Design (RBD) with five concentration treatments (0 ppm, 50 ppm, 100 ppm, 150 ppm, and 200 ppm) and five replications. The results showed that a concentration of 200 ppm Paclobutrazol gave the most significant inhibitory effect, reducing plant height by 33% compared to the control and producing fewer branches. However, yield variables such as biomass weight, pod weight, seed weight, and number of pods did not show significant differences between treatments. This indicates that Paclobutrazol is more dominant in inhibiting vegetative growth without providing a significant increase in the generative phase. This study concluded that the application of Paclobutrazol at high concentrations significantly inhibited the growth of mung beans but did not significantly affect the yield.